Soil water samples analyzed for dissolved iron (Fe) and other chemical compounds from several drained thaw lake basins near Barrow, Alaska, 2010 - D. A. Lipson (Arctic Data Center, 2013)
Soil water was collected from several drained thaw lake basins near Barrow, Alaska (AK) in 2010. Samples were collected from 0-10 centimeter (cm) depth using Rhizon soil moisture samplers and analyzed for dissolved iron (Fe), organic carbon, siderophores, carbon dioxide and methane (Lipson et al. (2013) Global Biogeochemical Cycles 27:1-11, doi:10.1002/gbc.20038).